Pencapaian Triple Eliminasi Pada Ibu Hamil Di Wilayah Puskesmas Banjar - Luh Made Ina Krishanty; putu dian prima kusuma dewi; Indrie Lutfiana (NERSMID : Jurnal Keperawatan dan Kebidanan, 2022)
Indonesia has a prevalence rate of these three diseases reaching 0.39% for HIV, 1.7% for Syphilis and 2.5% for Hepatitis B. With the large population of Indonesia, this figure is still included in the high number so more attention is needed to overcome it. This study aims to see the implementation of triple elimination in pregnant women. Research is a descriptive quantitative research with a cohort study and a retrospective approach. This descriptive research was used to examine the incidence of pregnancy at risk at the Banjar I Health Center by utilizing the maternal cohort register in the last 1 (one) year. The results showed that all pregnant women had non-reactive results in cases of STIs, HIV and Syphilis (425) 100%. Gestational characteristics in pregnant women with low risk, healthy reproductive age of 88.34% (303), distance less than 2 years 55.10% (189) with an average age of 38.9 weeks while the high risk group with unhealthy reproductive age of 68.29% (56), distance of more than 2 years 80.49% (66) with an average gestational age of 39.02 weeks. ANC visits in the irregular category with criteria of more than 30 days i.e. on visits 1 to 2 (293: 68.94%), Visits 2 to 3 (294: 69.18%), visits 3 to 4 (287: 67.53%), visits 4 to 5 (253: 59.53%).  The results of this study can be used as input for midwives in order to provide the right IEC and carry out early detection related to HIV disease. Syphilis dna Hepatitis B in every pregnancy .